The Gold Coast Integrated Care Model - Connor, Martin (Int J Integr Care, 2016)
This article outlines the development of the Australian Gold Coast Integrated Care Model based on the elements identified in contemporary research literature as essential for successful integration of care between primary care, and acute hospital services. The objectives of the model are to proactively manage high risk patients with complex and chronic conditions in collaboration with General Practitioners to ultimately reduce presentations to the health service emergency department, improve the capacity of specialist outpatients, and decrease planned and unplanned admission rates. Central to the model is a shared care record which is maintained and accessed by staff in the Coordination Centre. We provide a process map outlining the care protocols from initial assessment to care of the patient presenting for emergency care. The model is being evaluated over a pilot three year proof of concept phase to determine economic and process perspectives. If found to be cost-effective, acceptable to patients and professionals and as good as or better than usual care in terms of outcomes, the strategic intent is to scale the programme beyond the local health service.